SISTEM PAKAR MENDIAGNOSA PENYAKIT PADA MANUSIA YANG DISEBABKAN OLEH VIRUS (Information Technology and Telematics, 2014)
ABSTRACTsangat membantu dalam menyelesaikanpermasalahan mulai dari yang sederhanasampai yang kompleks. Hal inidibuktikan dengan banyaknya instansipemerintah, perusahaan-perusahaanbesar ataupun kecil, lembaga-lembagadibidang kesehatan, pendidikan dankemasyarakatan.Salah satu bentuk dariperkembangan komputer adalah semakindikembangkannya teknologi kecerdasanbuatan dalam aplikasi-aplikasikehidupan nyata yang berbasis dekstop.Dimana aplikasi tersebut hanya dimilikiinstansi kesehatan dan hanya beradapada komputer yang terinstal denganaplikasi sistem pakar tersebut. Untukmemudahkan para pakar kesehatan,aplikasi-aplikasi sistem pakar yangberbasis web ini lebih efektif dan efisienkarena bisa diakses dimanapun.Many people feel that when healthy , butunderweight people tend to not check her healthbecause of symptoms experienced is still relativelylightweight , cost constraints , where a doctor orhealth clinic so far resulted in the disease developsdue to lack of awareness of the illness and itsprevention . Of emerging technologies in themoment, it takes an application that is expected tohelp the community . Therefore made the diagnosisexpert system disease caused by web-based viruses.Diagnosis expert system disease caused by a viruscreated using PHP programming language anddatabase ( MySQL ) . Diagnosis expert systemdisease caused by a virus designed to use systemdesign tools . This expert system will provide someof the symptoms in the form of questions that willbe in the system so that we will get the result in theform of the solution as well as the type of diseaseand the cure .It can be concluded that the expert systemdiagnoses a disease caused by a virus has beendesigned and implemented with facilities includedisease diagnosis , user management , virusmanagement , medication management , symptommanagement , disease management and relationshipmanagement in the future will be used to diagnosedisease.Keywords: Expert System, Forward Chaining,PHP, MySQL, Ducks Disease.